Severe Preeclamptic Patients in The Resuscitation Room of Dr. Soetomo General Academic Hospital Surabaya: A Retrospective Study - Firmanto, Neissya Nastiti; Maulydia; Mulawardhana, Pungky; Fitriati, Mariza (Faculty of Medicine-Universitas Airlangga, 2022)
Introduction: Preeclampsia is the leading cause of maternal and fetal death. This is an urgency in maternal health, especially in developing countries such as Indonesia. Patients with severe preeclampsia who had critical conditions tend to be admitted to the resuscitation room for assistance from more skilled personnel and more sophisticated technology. Objective: This study aims to determine the complications, treatments, and outcomes of severe preeclampsia patients managed in the resuscitation room at Dr. Soetomo General Academic Hospital from January 1st, 2018 – December 31th 2019. Methods: The method used in this study was retrospective descriptive using medical records and analyzed using Microsoft Excel. Eighty-one samples met the inclusion criteria. Results: The majority of patients were aged 20-35 years (65.43%) and had completed senior high school (88.89%). Most patients were having stage 2 obesity (44.44%) and multigravida (41.97%). A history of preeclampsia and hypertension was not found in the majority of patients. Most patients are diagnosed with late-onset preeclampsia (69.14%). The majority of patients were referred from secondary health facilities (96.30%). The most common complication was pulmonary edema(53.09%). The majority of patients had 2 complications (43.17%) with the most common combinations being eclampsia and HELPP syndrome (13.58%). Intubation is given to the majority of patients (70.37%) and most often in patients with eclampsia (56.14%). Termination of pregnancy by cesarean section is carried out in the majority of patients (72.84%). There were no cases of maternal death in this study. Most of the fetal born had prematurity (70.11%), low birth weight (60%), and asphyxia as assessed by the first minute APGAR score (72.97%) and fifth minute APGAR score (54.05%). Conclusion: The majority of preeclampsia patients with complications in the resuscitation room at Dr. Soetomo General Academic Hospital Surabaya from January 1st 2018-December 31rd 2019 had good maternal outcomes but not the fetal outcome.